Transport Parameters and Dielectric Strength of Electrical Discharges in an Arc Discharges in Carbon Dioxide Gas - Idris H. Salih (Zanco Journal of Pure and Applied Sciences, 2020)
The two-term approximation solution of Boltzmann equation analysis has been used to calculate the electron energy distribution function (EEDF), dielectric strength and the electron swarm parameters in carbon dioxide. The electron swarm parameters have been calculated over the wide range of reduced density electric field strength E/N varying from 0.1 to 1000 Td ( 1Td= 10-17 V.cm2). These parameters, namely electron drift velocity, mean electron energy, electron temperature, characteristic energy, transverse diffusion coefficient, electron mobility, reduced ionization and attachment Townsend coefficients have been compared with the available previous theoretical and experimental results. The values of the critical reduced electric field strength (E/N)cr from the curves of reduced effective ionization coefficient (α-η)/N are calculated. In addition, excitation rate and fractional power transfer to elastic and inelastic collisions are explained.